Optimization Of Dynamic Transportation Task Assignment In A Manufacturing Facility - Tugiman, Muhammad Najib (2020)
In the present economy, manufacturing plants must have the able to work effectively and react rapidly to changes in the product mix and demand. Layout design significantly affects manufacturing effectiveness. At first, it was treated as a static decision yet because of progress in advances, it is conceivable to rearrange the manufacturing facilities in various situations. An extensive survey of the research work for dynamic layout planning has been embraced in this paper with an investigation of various algorithms to optimize it. Hybrid algorithm can likewise be utilized to improve the plant layout. An attempt has additionally been done to sort the writing with conceivable future research areas. This paper aims to manage the current and future patterns of research on facility layout issues dependent on past research including formulations, arrangement procedures, and the scope for utilization of hybrid algorithms. The utilization of new optimization procedures gives a point of view of future research in Dynamic facility layout issues and hybrid algorithms. A pattern toward multi-objectives approaches, developing facility layout software utilizing meta-heuristics, for example, simulated annealing (SA), genetic algorithm (GA), Anylogic Software and concurrent engineering to facility layout is observed. This paper is sorted out as follows; Chapter 2 gives a concise review of literature, on the Optimization of Dynamic Transportation Task. Segment 3, gives the procedure to this whole project